MiR‐34b‐5p inhibition attenuates lung inflammation and apoptosis in an LPS‐induced acute lung injury mouse model by targeting progranulin. Issue 9 (25th March 2018) - Xie, Wang; Lu, Qingchun; Wang, Kailing; Lu, Jingjing; Gu, Xia; Zhu, Dongyi; Liu, Fanglei; Guo, Zhongliang
Abstract : Inflammation and apoptosis play important roles in the initiation and progression of acute lung injury (ALI). Our previous study has shown that progranulin (PGRN) exerts lung protective effects during LPS‐induced ALI. Here, we have investigated the potential roles of PGRN‐targeting microRNAs (miRNAs) in regulating inflammation and apoptosis in ALI and have highlighted the important role of PGRN. LPS‐induced lung injury and the protective roles of PGRN in ALI were first confirmed. The function of miR‐34b‐5p in ALI was determined by transfection of a miR‐34b‐5p mimic or inhibitor in intro and in vivo. The PGRN level gradually increased and subsequently significantly decreased, reaching its lowest value by 24 hr; PGRN was still elevated compared to the control. The change was accompanied by a release of inflammatory mediators and accumulation of inflammatory cells in the lungs. Using bioinformatics analysis and RT‐PCR, we demonstrated that, among 12 putative miRNAs, the kinetics of the miR‐34b‐5p levels were closely associated with PGRN expression in the lung homogenates. The gain‐ and loss‐of‐function analysis, dual‐luciferase reporter assays, and rescue experiments confirmed that PGRN was the functional target of miR‐34b‐5p. Intravenous injection of miR‐34b‐5p antagomir in vivo significantly inhibited miR‐34b‐5p up‐regulation, reduced inflammatory cytokine release, decreased alveolar epithelial cell apoptosis, attenuated lung inflammation, and improved survival by targeting PGRN during ALI. miR‐34b‐5p knockdown attenuates lung inflammation and apoptosis in an LPS‐induced ALI mouse model by targeting PGRN. This study shows that miR‐34b‐5p and PGRN may be potential targets for ALI treatments. Abstract : miR‐34b‐5p participates in the development of acute lung injury by regulating progranulin.